La Grande Borne à Clermont-Ferrand (Puy-de-Dôme) : un monument funéraire de la première moitié du iie s. apr. J.-C. en contexte rural - Frédérique Blaizot; Pierre Caillat; Alain Wittmann; Gérard Vernet (Gallia)
The archaeological site of La Grande Borne is located 5 km east of the present-day town of Clermont-Ferrand. The archaeological map data allow to place the funerary monument in question at a crossroad, probably in the territory of a villa. Its first state of construction, dated from the first half of the 2nd c. AD, remains unknown, but it is at the origin of a small burial area that has been in use until the end of 3rd c. Rebuilt in the second half of the 2nd c., the monument consisted of an enclosure whose walls were adorned with painted plaster, with one altar at least that contained one ossuary.